SIMULATION OF RAINBOW VERTEX CONNECTION ON GRAPH OF THE CORONA PRODUCT OF TWO TREE GRAPHS - Eka Pranata, Widya
Graph ???? is a pair of sets (????,????) where ???? is a set of vertices and ???? is a set of edges. The corona product of two graphs ???? and ???? is defined as a graph obtained from duplicating graph ???? to each point of ???? and it is denoted by ?????????. A path ???? is said to be a rainbow vertex path if the internal points in the path ???? are colored differently. The coloring of vertices on a graph ???? are said to be rainbow vertex connected if for every ???? and ???? in ????(????) there is a rainbow (vertex) path. Algorithms are logical steps to solve a systematically structured problem. This study constructed a rainbow vertex coloring algorithm on a tree graph and the corona product of two tree graphs. The algorithm is implemented into a programming language to determine the coloring of rainbow connected graphs of tree and the corona product of trees.